Identification of parasitic forms in public transport vehicles in the city of São Mateus, Espírito Santo, Brazil - Miossi, Jamille Santos; Barros, Rafaela Souza; Andrade de Souza, Marco Antônio (Brazilian Journal of Production Engineering, 2021)
Introduction. One of the major concerns of public health agencies is the incidence of parasitic diseases, especially in developing countries, such as Brazil. These diseases are associated with several factors such as the lack of knowledge of the population regarding health education, the incorrect destination of waste, lack of basic sanitation and numerous processes of environmental contamination. Objective. To evaluate the contamination by forms of enteroparasites in bus routes in the city of São Mateus. Methodology. The method used in this study was that of Graham, with modifications, that consists in the apposition of tape in tactile supports, turnstiles, entrances and exits of the buses, all in average estimated heights at the reach of the hands and later deposition in glass slides by direct contact. The obtained material was analyzed in the Laboratório de Parasitologia e Hematologia Clínica of the Universidade Federal do Espírito Santo, campus São Mateus under light microscope (10X and 40X), without any addition of dyes. Results. A total of seventy-two samples were analyzed, distributed among the eight public transport lines selected in the study. The results indicated the contamination of 50% of the vehicles analyzed and the main parasites and commensal were Balantidium coli, Iodamoeba butschlii and Entamoeba coli. Conclusions. Public transportation buses in the city of São Mateus have potential for human contamination and can createrisks for the population that uses this service.